Safer solutions in sport and leisure responsibilities for crowd management at major events : delegate information : 5 April 2001 (Thomas Telford, 2001)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held at Old Trafford, Manchester on 5 April 2001.